(untitled) (Fiep Bulletin - online, 2024)
Of a philosophical nature, this essay is intended not only to provide a conceptual reflection on the body and movement through the ages, but also to reflect discussions on the subject in the academic world, from an up-to-date perspective of knowledge in the holistic framework and complexity that inhabits us. In view of this, this study re-read the philosophical thoughts and conceptions of the body, with the chosen specialists on the subject, from the classical Greek era to modern times. The bibliographic selection is relevant because it guarantees a worthy discussion of the subject, through overlapping ideas and value judgments on the subject of the body and movement, clarifying the value of this qualitative study. Considering all of the above, it induces us to think from another perspective, adjectivized and embodied in new values and new formulations about corporeality and human motricity.